2013
DOI: 10.1158/1055-9965.epi-12-1196-t
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Fat, Fatty Acids, and Risk of Prostate Cancer in the NIH-AARP Diet and Health Study

Abstract: Background Observational studies report inconsistent associations of fat and fatty acids with prostate cancer. Methods We investigated associations between dietary fats and fatty acids and risk of prostate cancer in the National Institutes of Health (NIH)-AARP Diet and Health Study. Diet was assessed at baseline with self-administered food-frequency questionnaires. Cases were determined by linkage with state cancer registries. Hazard ratios (HR) and 95% confidence intervals (CIs) were estimated with Cox prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
92
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(98 citation statements)
references
References 42 publications
3
92
0
3
Order By: Relevance
“…The accompanying meta-analysis of the 7 studies available at the time also showed no risk relation [276] (LOE IIa). Furthermore, both the NIH-AARP Study [277] (LOE IIb) and the Melbourne Collaborative Cohort Study [278] (LOE IIb) reported no change in risk associated with a modified fat intake.…”
Section: Quantity and Quality Of Dietary Fat And Fatty Acid Intakementioning
confidence: 99%
See 1 more Smart Citation
“…The accompanying meta-analysis of the 7 studies available at the time also showed no risk relation [276] (LOE IIa). Furthermore, both the NIH-AARP Study [277] (LOE IIb) and the Melbourne Collaborative Cohort Study [278] (LOE IIb) reported no change in risk associated with a modified fat intake.…”
Section: Quantity and Quality Of Dietary Fat And Fatty Acid Intakementioning
confidence: 99%
“…Basset et al [278] (LOE IIb) reported no association between SFA intake and risk of prostate cancer in the Melbourne Collaborative Cohort Study . In the NIH-AARP Study , the evaluation on this subject also found no association when all prostate carcinomas were investigated [277] (LOE IIb). In this study, however, a positive association with the level of SFA intake was found both for advanced stage carcinomas and fatal carcinomas [277] (LOE IIb).…”
Section: Quantity and Quality Of Dietary Fat And Fatty Acid Intakementioning
confidence: 99%
“…Studies looking at fatty acid intake were mainly based, until now, on data gathered from food-frequency questionnaires (FFQ; refs. 18,19), with few studies based on fatty acid profiles measured in plasma circulating lipids (13,20) and even fewer studies in which fatty acids were measured in the membranes of red blood cells (RBC; refs. 21,22).…”
Section: Introductionmentioning
confidence: 99%
“…In transgenic mice in which males develop prostate cancer, n-3 PUFA intake from marine sources suppressed tumorigenesis [80]. This is also the case in people where there is reduced risk of developing prostate cancer with increased intake of marine n-3 PUFAs [81][82][83]. Longer chain n-3 PUFAs from non-marine sources, however, are associated with an increased risk of prostate cancer [79,82,83].…”
Section: Cancer Associations With Faty Acidsmentioning
confidence: 99%